2021
DOI: 10.21037/atm-21-4481
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte activation gene-3 is associated with programmed death-ligand 1 and programmed cell death protein 1 in small cell lung cancer

Abstract: Background: In recent years, immunotherapy has achieved notable success in cancer treatment. Indeed, the novel immune checkpoint lymphocyte activation gene-3 (LAG3) has shown promising therapeutic efficacy in non-small cell lung cancer. However, it is unclear about the role of LAG3 in immunotherapy and survival in small cell lung cancer (SCLC). Methods:The expression of LAG3 in SCLC was evaluated in four public datasets. The association of LAG3 with programmed death-ligand 1 (PD-L1), programmed cell death pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Immunotherapies represent a major advance in the management of SCLC. Several novel targets, which have been discovered due to our deepening understanding of the immunological milieu of SCLC, include TIM-3, TIGIT and LAG3 [ 172 174 ], as demonstrated in Fig. 5 A. Sun’s study has revealed the expression of LAG3 in SCLC tumor tissues.…”
Section: Tumor-intrinsic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapies represent a major advance in the management of SCLC. Several novel targets, which have been discovered due to our deepening understanding of the immunological milieu of SCLC, include TIM-3, TIGIT and LAG3 [ 172 174 ], as demonstrated in Fig. 5 A. Sun’s study has revealed the expression of LAG3 in SCLC tumor tissues.…”
Section: Tumor-intrinsic Factorsmentioning
confidence: 99%
“…Significantly, LAG3 expression was linked with immune-associated biological processes including immune response, antigen presentation, and T cell co-stimulation. They demonstrated that LAG3 is a vital immune checkpoint closely related with PD-1/PD-L1[ 174 ]. Therefore, LAG3 holds as an appealing novel immunological target for SCLC.…”
Section: Tumor-intrinsic Factorsmentioning
confidence: 99%
“…The expression of LAG on tumors was established by the TCGA, showing that its expression on various tumors has a direct effect on prognosis. Hui sun et al conducted a study in a cohort of SCLC patients showing the LAG-3 expression in the tumor tissues and its association with PD-1 expression [142]. Thus, the development of a molecule targeting the LAG-3 checkpoint might prove to be efficacious.…”
Section: Clinical Trials Of Various Icis Targeting Immune Checkpointsmentioning
confidence: 99%
“…LAG-3+ TILs are prevalent in two broad histological subtypes of lung cancer: small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC), which include adenocarcinoma, squamous cell carcinoma and large cell carcinoma [ 53 ]. GSE149507 cohort study revealed that LAG-3 levels were significantly overexpressed in all samples from SCLC patients compared with healthy lung tissues [ 55 ]. Similar tendencies were observed in a study conducted on 53 patients with NSCLC, where intratumoral Treg cells presented higher levels of immunosuppressive molecules, such as LAG-3, CTLA-4 and PD-1 than Tregs from tumor-adjacent tissues or peripheral blood Treg cells [ 56 ].…”
Section: Lag-3 In Neoplasmsmentioning
confidence: 99%
“…In a study conducted by Ma et al LAG-3-expressing CD4+CD25- T cells infiltrated the resected tumors and were more common in metastases than in primary tumors [ 57 ]. Evidence suggests that in lung tumors overexpression of LAG-3, PD-1 and TIM-3 is connected with prominent T cell activation (CD69/CD137), effector function (Granzyme-B), and proliferation (Ki-67), but also with elevated levels of proapoptotic markers (FAS/BIM) [ 55 , 58 ]. An increased number of Treg cells and higher expression of inhibitory molecules may have a crucial role in the anti-tumor immune response in NSCLC patients, which may contribute to tumor immune escape and tumor progression [ 56 ].…”
Section: Lag-3 In Neoplasmsmentioning
confidence: 99%